The placement of elderly persons - a logit estimation and cost-analysis - O'Shea, Eamon; Corcoran, Rosaleen (Economic & Social Studies, 1989)
This study focuses on two groups of elderly persons deemed by the relevant health professional to be on the margin of domiciliary care and institutional care, respectively. A logit regression is estimated in order to test for significant factors that may be important in determining the current placement of those elderly persons. The formal and informal costs of care are enumerated and valued, in monetary terms, for the domiciliary based group. Some suggestions are made with regard to current and future placement decision-making for elderly persons. In particular, it seems increasingly inappropriate to treat informal care as a free good given the range of opportunity costs identified by carers.
Keywords: Elderly; Carers; Ageing society - Economics